2013
DOI: 10.1111/cge.12297
|View full text |Cite
|
Sign up to set email alerts
|

Aminoacylase I deficiency due to ACY1 mRNA exon skipping

Abstract: Aminoacylase 1 (ACY1) deficiency is a rare inborn error of metabolism of which less than 20 observations have been described. Patients exhibit urinary excretion of specific N-acetyl amino acids and manifest a heterogeneous clinical spectrum including intellectual disability, motor delay, seizures, moderate to severe mental retardation, absent speech, growth delay, muscular hypotonia and autistic features. Here, we report the case of ACY1 enzyme deficiency in a 6-year-old girl presenting severe intellectual dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Although no previous studies, to the best of our knowledge, have suggested that there is an association between ACY1 expression and the severity of colorectal cancer, the results of the current study demonstrated that the level of ACY1 mRNA and protein is positively associated with the TNM stage of the tumor. Previously, ACY1 has been widely recognized for its catalytic activity in the acylation of N-terminal amino acids (6)(7)(8)(20)(21)(22). ACY1 is widely expressed in different organs and previous studies have shown that in the human digestive tract ACY1 is particularly abundant in epithelial cells, but not in stromal cells (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no previous studies, to the best of our knowledge, have suggested that there is an association between ACY1 expression and the severity of colorectal cancer, the results of the current study demonstrated that the level of ACY1 mRNA and protein is positively associated with the TNM stage of the tumor. Previously, ACY1 has been widely recognized for its catalytic activity in the acylation of N-terminal amino acids (6)(7)(8)(20)(21)(22). ACY1 is widely expressed in different organs and previous studies have shown that in the human digestive tract ACY1 is particularly abundant in epithelial cells, but not in stromal cells (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The cocktail was subsequently incubated for 5 min at room temperature and added to the cells. The transfection system was kept at 37˚C in 5% CO 2 for 48 h (20)(21)(22). After 48 h, downregulation of ACY1 was measured by qPCR.…”
Section: Methodsmentioning
confidence: 99%
“…Values ranging from 0.7 to 1.3 were assumed to be normal based on our previous experience. 20,21 Ten control DNAs and two DNAs from two previously described female relatives of a BTHS patient harbouring a heterozygous deletion of TAZ exons 6-11 (NG_009634.1:g.[9777_9814del; 9911-?_14402del] 4 ) were included in order to validate the assay.…”
Section: Determination Of the X-chromosome Linkage And X-inactivationmentioning
confidence: 99%
“…Aminoacylase 1 (ACY1, EC 3.5.1.14) deficiency (MIM 609924) is a rare inborn error of metabolism (IEM) characterized by increased urinary excretion of N-acetylated amino acids with the exception of N-acetylaspartic acid (NAA). Since the first report by Van Coster et al (2005) less than 20 additional patients have been described, most of them presenting with heterogeneous neurological symptoms such as psychomotor delay, seizures, intellectual disability (Sass et al 2007;Ferri et al 2013). ACY1 deficiency has also been reported associated with autistic feature in one patient (Tylki-Szymanska et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…ACY1 is located on the short arm of chromosome 3 (3p21.1) (Naylor et al 1979(Naylor et al , 1982Miller et al 1990;Cook et al 1993), and the protein is highly conserved, supporting an evolutionary role in physiology. Until now ten different mutations have been reported (Van Coster et al 2005;Sass et al 2006Sass et al , 2007Tylki-Szymanska et al 2010;Ferri et al 2013), with no clear-cut phenotype-genotype correlation.…”
Section: Introductionmentioning
confidence: 99%